Lesions of the Eyelid: A 5 - year Retrospective Study in a Tertiary Care Centre - Toppo, Anupa; Sahu, Alaka; Pradhan, Ipsita; Agrawal, Kailash Chandra (Annals of Pathology and Laboratory Medicine, 2019)
Background: Eyelid oncology is of utmost importance. Eyelid lesions are rarely lethal and completely treatable if detected early. Overview of eyelid lesions guides ophthalmogists to design for optimal therapy. Materials and methods: A retrospective analysis of eyelid lesion was done from 2013 to 2018 in the department of pathology, VSSIMSAR, Burla, Odisha, confirmed through histopathology. Data regarding age, sex and topography of lesion were also included. Results: A total of 104 biopsies were evaluated. Male to female ratio were 1:1.16 for benign tumours and 1:1.36 for malignant tumours. The age of the patient at the time of biopsies ranged from Â½ year to 78 years old. The most common benign eyelid lesion encountered in our practice was epidermoid cyst followed by vascular haemangioma. Conclusion: The majority of eyelid lesions were benign eyelid tumours while malignant eyelid tumours contributed 25% of total eyelid lesions. Sebaceous gland carcinoma was the most common eyelid tumour found in the present study that was consistent with other studies for Asian countries.